Pengembangan Lembar Kerja Siswa Melalui Model Blended Learning Berbasis Budaya Melayu Sambas Materi Aritmatika Sosial Kelas VII SMP - Tasa, Jasmin Loise (CARTESIUS : Jurnal Pendidikan Matematika, 2019)
This study aims to 1) find out the validity of Student Worksheets (LKS) through the Blended Learning model based on Sambas Malay culture, 2) find out the effectiveness of Student Worksheets (LKS) through the Blended Learning model based on Sambas Malay culture so that it can be used to study Arithmetic material Social in class VII of junior high school. This study uses the research and development method or research and development (R & D) development model of ADDIE with stages (1) Analysis (Analysis), (2) Design (Design), (3) Develop (Development), (4) Implement (Implementation) , (5) Evaluation. Based on data analysis and discussion, data obtained from material expert validation were obtained with an average total rating of 4.2 in the good category so that the Student Worksheet (LKS) was said to be valid. From the results of the study, it was found that the effectiveness of Student Worksheets (LKS) through the Blended Learning model based on Sambas Malay culture obtained several judgments through the learning outcomes test as follows: 1) Student learning completeness in a classical manner was 85.18% in the complete category; 2) Achievement of competency indicators with a percentage of 83.52% in the complete category; 3) The results of the observation of the teacher's ability to manage learning with an average value of 3.75 are in the excellent category; 4) Effective learning time for 4 meetings; 5) Questionnaire of student responses to LKS with an average rating of 4.52 in the positive category. Based on the analysis of the above data, it can be concluded that Student Worksheets (LKS) developed through the Blended Learning model based on Sambas Malay culture of Social Sciences Arithmetic class VII SMP are valid and effective to be used to support mathematics learning